Policy Issues for the ASEAN Economic Community: the Rules of Origin - Josef T. Yap; Erlinda M. Medalla (Philippine Institute for Development Studies (PIDS), 2008)
Striking a balance between trade facilitation and preventing trade deflection is the single most difficult challenge with regard to the issue of rules of origin (ROO). ASEAN ROO is already considered as among the simplest in the world and still, in practice, results fall short of expectations. ASEAN is fully cognizant that in order to achieve its goal of a single market and production base, progress in eliminating tariffs within ASEAN is not enough. It needs to be accompanied by an enabling ROO regime. Indeed, the AEC Blueprint explicitly provides for instituting reforms in ASEAN ROOs toward the direction of less restriction and simplification. In the medium term, ASEAN member countries can push for an East Asia Free Trade Area that will consolidate the various bilateral and subregional FTAs and therefore overcome the noodle bowl syndrome. This would be a direct result of harmonizing the various ROOs. It goes without saying that the ultimate or long-term objective would be an equitable and efficient multilateral trading system anchored on lower MFN rates under the auspices of the WTO.
Keywords: 330; rules of origin; free trade agreements (FTAs); ASEAN Economic Community (AEC); Herkunftsbezeichnung; Freihandelszone; ASEAN-Staaten